Strategi Implementasi Perubahan Organisasi: Pendekatan Manajemen Perubahan yang Efektif - Said Ihsan Fauzi; Chuzaimah Batubara (Universitas Muhammadiyah Enrekang, 2023)
This abstract discusses the strategy of implementing organizational change with an effective change management approach. Its purpose is to introduce the basic concepts and principles of change management to help organizations achieve their goals and overcome the challenges of change. An effective change management approach involves five main steps: evaluating the situation, planning change, implementing change, monitoring and evaluating results, and correcting and strengthening changes. In addition, it is important for the organization to establish a change management team consisting of individuals who are experienced in change management. In the deployment of organizational change, effective communication is essential to ensure a clear and consistent understanding of the change. The implications of implementing an effective change management strategy will assist organizations in dealing with change with an adaptive and innovative attitude so as to improve overall organizational performance.